The Effect of Alternating Current Iontophoresis on Rats with the Chronic Constriction Injury to the Infraorbital Nerve - Yoko Yamazaki; Masahiro Umino; Haruhisa Fukayama; Masahiko Shimada (Hindawi Limited, 2012)
This study aimed to examine the effect of AC iontophoresis on rats with the chronic constriction injury (CCI) to the infraorbital nerve by animal experiments. CCI model rats were divided into four groups, namely, rats that received general anesthesia for 60 min except AC IOP (CCI: n=5), AC IOP with 0.9% physiological saline for 60 min (CCI + saline AC IOP: n=5), AC IOP with 4% lidocaine hydrochloride for 60 min (CCI + lidocaine AC IOP: n=5), and attachment of two electrodes soaked with 4% lidocaine hydrochloride to the facial skin for 60 min (CCI + attach lidocaine: n=5). In the CCI + lidocaine AC IOP group, an elevated withdrawal threshold was observed after AC IOP, and the duration of efficacy was longer compared with that in the CCI + saline AC IOP and CCI + attached lidocaine groups. A significant decrease in the number of Fos-like immunoreactive (LI) cells was observed in the CCI + lidocaine AC IOP group compared with that in the CCI group. These findings suggest that the effect of CCI + lidocaine AC IOP group may be caused by active permeation of lidocaine into the facial skin and electrical stimulation of the trigeminal nucleus.